Some issues of improving the electoral law of the Republic of Kazakhstan: analysis of judicial practice - Yerzhanova, F.A.; Zhamiyeva, R.M.; Ilyassova , G.A. (Bulletin of the Karaganda University “Law Series”, 2020)
The article discusses the problems of applying substantive and procedural law in the field of electoral activities, the legal framework for protecting the electoral rights of citizens, and requirements for the subjects of the electoral process. Determined the essence of certain election procedures, in particular, related to the decision about refuse to register candidates for deputies, exclusions from the list of candidates, or to refuse to reinstate in the list of candidates. Given the analysis to provisions in the Constitutional Law of the Republic of Kazakhstan «About Elections in the Republic of Kazakhstan», to civil law norms about election law, investigated the legal scholars’ positions of regarding to the problems of constitutional legal responsibility. The novelty of the article is that by studying the current legislation, a comprehensive analysis of the procedure for considering citizens' complaints was carried out and measures were determined to improve the procedure for their adoption and consideration in electoral bodies. Proposed to adopt a special Decree of the Supreme Court about the application of election legislation, to eliminate some gaps in the election legislation. Formulated the conclusions about the need to further improve the institutions of the electoral law and the process, through which the guarantees are implemented in the field of electoral rights of citizens.